Snoring in individuals with and without maxillary constriction. - Marcos J. Carruitero; Zandalee A. Escobedo-Terrones (Universidad de Concepción., 2018)
Objective: compare snoring in individuals with and without maxillary constriction. Methods: 124 individuals (mean age, 40.53; SD, 15.59), 81 women and 43 men were evaluated. Two groups were formed, 62 individuals with and 62 without maxillary constriction. To assess the snoring, a visual analog scale of snoring severity was used. Comparison of snoring scores between groups was performed by the U Mann-Whitney test. Simple and multiple linear regressions were also performed. Results: The mean snoring scores of the group with maxillary constriction was 3.00+/-2.96, while in the group without maxillary constriction it was 3.87+/-2.90. No statistically significant differences between snoring scores in individuals with and without maxillary constriction was found (p=0.105). The variability of snoring scores was not explained by the presence of maxillary constriction (p=0.100, R2=2.20%). Conclusion: There was no different between the snoring scores in individuals with and without maxillary constriction. Maxillary constriction alone does not influence snoring.